Inflammation and mitochondrial dysfunction: A vicious circle in neurodegenerative disorders?. (25th September 2019) - van Horssen, Jack; van Schaik, Pauline; Witte, Maarten
Highlights: Both mitochondrial dysfunction and neuroinflammation contribute significantly to neurodegenerative diseases. Multiple inflammatory mediators are known to affect in mitochondrial energy metabolism and mitochondrial dynamics. In turn, mitochondrial dysfunction can promote inflammation. Abstract: Experimental evidence supports an intricate association between inflammation and mitochondrial dysfunction as main contributors of neurological diseases. Inflammatory mediators produced by activated microglia and infiltrated immune cells trigger intracellular signalling cascades that can alter cellular mitochondrial metabolism. Cytokines, particularly tumor necrosis factor-alpha, impede mitochondrial oxidative phosphorylation and associated ATP production and instigate mitochondrial reactive oxygen species production. This culminates in mitochondrial membrane permeabilization, altered mitochondrial dynamics and might ultimately result in cell death. When severely injured mitochondria are not appropriately removed by mitophagy they can release their contents into the cytosol and extracellular environment and thereby amplify the inflammatory process. Here we provide a comprehensive overview on how inflammatory mediators impair mitochondrial metabolism and discuss how defective mitochondria can elicit and potentiate an inflammatory response.